Mothers' considerations in snack choice for their children: Differences between the North and the South of Italy. (October 2020) - Damen, Femke W.M.; Luning, Pieternel A.; Pellegrini, Nicoletta; Vitaglione, Paola; Hofstede, Gert Jan; Fogliano, Vincenzo; Steenbekkers, Bea L.P.A.
Highlights: A snack needs to be liked by the child, otherwise Italian mothers do not provide it. North Italian mothers seem to be more health-conscious. South Italian mothers relate healthiness of snacks to giving energy. The brand is more important for mothers in the South of Italy. Mothers in the North of Italy experience more value conflicts, all health-related. Abstract: This study describes differences in considerations and value conflicts between mothers living in the North and the South of Italy during snack provision to their 2–7 years old children. Semi-structured interviews with 20 mothers living in the North and 20 mothers living in the South of Italy were conducted. Participants matched on educational level and weight status. Mothers' considerations in snack provision were grouped into four key themes: health-related, child-related, time-related, and product-related. North Italian mothers showed more health-related considerations while providing a snack compared to mothers living in the South. In case mothers from the South mentioned healthiness as a consideration, it was often related to giving energy. The child-related key theme revealed that a snack needs to be liked by the child, otherwise Italian mothers do not provide it. For the time-related key theme, differences were small between North and South Italian mothers. The product-related key theme showed the brand to be more important for South Italian mothers. Mothers from the North of Italy experienced more value conflicts, all related to health. The current studied showed that even within the same country, geographical differences in mothers' considerations and value conflicts for providing snacks exist. This implies that snack choice, considerations and values seem to be influenced by tradition and family culture.